2009
DOI: 10.1016/s1875-9572(09)60064-4
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition-associated Cholestasis in Premature Babies: Risk Factors and Predictors

Abstract: Young gestational age, low birth body weight, more sepsis episodes, and long duration of parenteral nutrition were significant risk factors for PNAC in our study. Low energy intake during the 2nd and 3rd weeks of life is a predictor for PNAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 22 publications
6
45
2
1
Order By: Relevance
“…In a study examining the effect of fluconazole prophylaxis in low-birth-weight neonates [14], the incidence of cholestasis was 31% overall and cholestatic infants showed significantly lower birth weights; however, a multivariate analysis failed to reveal a significant association between birth weight and the development of cholestasis. Similarly, Hsieh et al [15] found that gestational age and birth weight were not identified as independent risk factors in his study. The lack of correlation in these latter studies may be caused by other confounding factors having greater predictive weight in predisposing infants to PNAC.…”
Section: Does Prematurity or Low Birth Weight Increase The Risk Of Dementioning
confidence: 68%
“…In a study examining the effect of fluconazole prophylaxis in low-birth-weight neonates [14], the incidence of cholestasis was 31% overall and cholestatic infants showed significantly lower birth weights; however, a multivariate analysis failed to reveal a significant association between birth weight and the development of cholestasis. Similarly, Hsieh et al [15] found that gestational age and birth weight were not identified as independent risk factors in his study. The lack of correlation in these latter studies may be caused by other confounding factors having greater predictive weight in predisposing infants to PNAC.…”
Section: Does Prematurity or Low Birth Weight Increase The Risk Of Dementioning
confidence: 68%
“…Hence, our study population was broad and included specific surgical diagnoses that are not classically associated with prolonged PN administration. Unlike other recently published data, however, this study did not exclude subjects based on gestational age, birth weight, surgical diagnosis, or duration of PN [12][13][14]. The data were collected before the implementation of new parenteral lipid minimization regimens and the use of ω-3 fatty acid supplementation to determine our baseline incidence of cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…These include an early emphasis on enteral nutrition, revised guidelines for caloric allotment in the critically ill infant, new elemental formulas for children with feeding intolerance, and the administration of ursodiol for hyperbilirubinemia [6][7][8][9][10][11]. Despite this progress in pediatric nutrition, new data on PNassociated cholestasis are lacking, and recent data have focused primarily on specific subgroups of neonates [12][13][14].…”
mentioning
confidence: 99%
“…89 Most of the data on children have been derived from studies of hospitalized premature or newborn infants. An increased risk of IF/PNALD was associated with young gestational age, 90 91,103 An appropriate PN regimen is also important as high parenteral energy intake, 88,95,104 use of a soybean-based lipid emulsion at a dose of >1 g/kg, 53 dextrose infusion >7 mg/ kg/min, 84,105 high amino acid load in premature infants, 90 as well as deficiency of transsulfuration pathway products, most notably choline, 106 have been reported to favour the development of IF/ PNALD. The use of lipid emulsion with a low content of omega-6 fatty acids is recommended both in preventing and treating IF/ PNALD.…”
Section: Patient Populationmentioning
confidence: 99%